Optimization and Biopharmaceutical Evaluation of Sustained-Release Macitentan Pellets Using Polymeric Coating and Box–Behnken Design - Mishra, Abhay Kumar; S, Rajasekaran (Journal of Neonatal Surgery, 2025)
Macitentan, an endothelin receptor antagonist widely used for the long-term management of pulmonary arterial hypertension (PAH), exhibits poor aqueous solubility, extensive first-pass metabolism, and variable plasma concentrations when delivered through conventional immediate-release formulations. These limitations justify the development of a sustained-release (SR) multiarticulate delivery system to achieve prolonged therapeutic exposure, reduced dosing frequency, and improved patient adherence. This study aimed to formulate, optimize, and evaluate sustained-release Macitentan pellets using a polymeric coating system and a Quality by Design (QbD) approach employing the Box–Behnken Design (BBD). Preformulation studies including solubility profiling, FTIR, DSC, and PXRD confirmed the physicochemical integrity of Macitentan and its compatibility with selected excipients such as microcrystalline cellulose (MCC), hydroxypropyl methylcellulose (HPMC), and ethyl cellulose (EC). Pellets were prepared through extrusion–spherization and coated with EC–HPMC blends to modulate drug release kinetics. A three-factor, three-level BBD—evaluating polymer ratio (X1), coating level (X2), and spherization time (X3)—was applied to study their effect on % drug release at 12 h (Y1), sphericity index (Y2), and friability (Y3). Statistical modelling demonstrated significant contributions of all variables (p < 0.05), with strong predictive power (R² > 0.98). The optimized formulation containing an EC:HPMC ratio of 3:1, coating level of 10%, and spheronization time of 12 min achieved a controlled release of ~78% at 12 h and >95% at 24 h, following zero-order kinetics and anomalous (non-Fickian) diffusion. In-silico pharmacokinetic simulation revealed reduced Cmax, prolonged Tmax, and increased mean residence time compared with immediate-release formulations, indicating improved plasma stability and suitability for once-daily administration. Accelerated stability studies performed as per ICH Q1A(R2) confirmed the formulation’s robustness with no significant change in assay, dissolution, or physical properties. Overall, the optimized sustained-release Macitentan pellets demonstrate strong potential as an improved therapeutic delivery system for chronic PAH management, with advantages in biopharmaceutical performance, dosing convenience, and patient compliance.